Scintillation time-scale measurement of the highly active FRB20201124A. Issue 3 (10th November 2021) - Main, R A; Hilmarsson, G H; Marthi, V R; Spitler, L G; Wharton, R S; Bethapudi, S; Li, D Z; Lin, H-H
ABSTRACT: Scintillation of compact radio sources results from the interference between images caused by multipath propagation, and probes the intervening scattering plasma and the velocities of the emitting source and scattering screen. In FRB20201124A, a repeating fast radio burst (FRB) that entered a period of extreme activity, we obtained many burst detections in observations at the upgraded Giant Metrewave Radio Telescope (uGMRT) and the Effelsberg 100-m Radio Telescope. Bursts nearby in time show similar scintillation patterns, and we measure a scintillation time-scale of 14.3 ± 1.2 and 7 ± 2 min at Effelsberg (1370 MHz) and uGMRT (650 MHz), respectively, by correlating burst pair spectra. The scintillation bandwidth scaled to 1 GHz is 0.5 ± 0.1 MHz, and the inferred scintillation velocity at Effelsberg is $V_{ISS}≈ (59± 7) \sqrt{d_{ l}/2\, \rm {kpc}}~{\rm km~s}^{-1}$, higher than Earth's velocity for any screen beyond a lens distance of $d_{ l} \gtrsim 400\, $ pc. From the measured scintillation bandwidth, FRB20201124A has comparatively lower scattering than nearby pulsars, and is underscattered by a factor of ∼30 or ∼1200 compared to the NE2001 and YMW16 model predictions, respectively. This underscattering together with the measured scintillation velocity is consistent with a scattering screen more nearby the Earth at $d_{ l} \sim 400\, $ pc, rather than at 2 kpc spiral arm that NE2001 predicts to be the dominant source of scattering. With future measurements, the distance, geometry, and velocity of the scattering screen could be obtained through modelling of the annual variation in V ISS, or through interstation time delays or interferometric observations. Scintillation/scattering measurements of FRBs could help improve Galactic electron density models, particularly in the Galactic halo or at high Galactic latitudes.